Influence of load ratio on torsion very high cycle fatigue of high‐strength spring steel in the presence of detrimental defects. Issue 9 (31st May 2021) - Karr, Ulrike; Schönbauer, Bernd M.; Sandaiji, Yusuke; Mayer, Herwig
Abstract: The influence of mean shear stress on torsion very high cycle fatigue (VHCF) for internal inclusion‐initiated fracture is investigated. Ultrasonic torsion fatigue tests are performed at load ratios R  = −1, 0.1, and 0.35 with high‐strength spring steel SWOSC‐V featuring an increased number of nonmetallic inclusions. Based on Murakami and Endo's area parameter model, an equation predicting the torsion fatigue limit in the presence of detrimental defects is rendered. Stress biaxiality is considered using a ratio of torsion to axial fatigue strength of τ a / σ a  = 0.86. Considering the load ratio sensitivity according to ([1 −  R ]/2) α, the value for α is experimentally determined to be 0.550. A fine granular area (FGA) is generated at an artificial surface defect in a fully reversed cyclic torsion test in vacuum. Measured growth rates in the FGA were 10 −14 –10 −12  m/cycle, and the formation of the FGA consumed 98% of the VHCF lifetime.